One Union, One Story? In Praise of Europe’s Narrative Diversity - Nicolaidis, K; Pelabay, J (Palgrave Macmillan, 2008)
“One Union, One Story? In Praise of Europe’s Narrative Diversity” w/ Janie Pelabay in Alex Warleigh-Lack, eds Reflections on European Integration, Palgrave 2008